Polycyclic aromatic hydrocarbons within airborne particulate matter (PM2.5) produced DNA bulky stable adducts in a human lung cell coculture model. Issue 2 (13th September 2011) - Abbas, Imane; Garçon, Guillaume; Saint‐Georges, Françoise; Andre, Véronique; Gosset, Pierre; Billet, Sylvain; Goff, Jérémie Le; Verdin, Anthony; Mulliez, Philippe; Sichel, François; Shirali, Pirouz
ABSTRACT To extend current knowledge on the underlying mechanisms of air pollution particulate matter (PM2.5)‐induced human lung toxicity, the metabolic activation of polycyclic aromatic hydrocarbons (PAH) within PM2.5 and PAH–DNA bulky stable adduct patterns in human alveolar macrophage (AM) and/or human lung epithelial L132 cells in mono‐ and cocultures were studied. In the coculture system, only human AM were exposed to air pollution PM2.5, unlike L132 cells. Particles, inorganic fraction and positive controls [i.e. TiO2, thermally desorbed PM (dPM) and benzo[a]pyrene, B[a]P, respectively] were included in the experimental design. Cytochrome P450 (CYP) 1A1 gene expression, CYP1A1 catalytic activity and PAH–DNA bulky stable adducts were studied after 24, 48 and/or 72 h. Relatively low doses of PAH within PM2.5 induced CYP1A1 gene expression and CYP1A1 catalytic activity in human AM and, thereafter, PAH–DNA bulky stable adduct formation. Adduct spots in PM2.5‐exposed human AM were higher than those in dPM‐exposed ones, thereby showing the incomplete removal of PAH by thermal desorption. PAH within air pollution PM2.5 induced CYP1A1 gene expression but not CYP1A1 catalytic activity in L132 cells. However, despite the absence of PAH–DNA bulky stable adduct in L132 cells from human AM/L132 cell cocultures exposed to dPM2.5 or PM2.5, reliable quantifiable PAH–DNA bulky stable adducts were observed in L132 cells from human AM/L132 cell coculture exposed to B[a]P. Taken together, these results support the exertion of genotoxicity of highly reactive B[a]P‐derived metabolites produced within human AM not only in primary target human AM, but also in secondary target L132 cells. Copyright © 2011 John Wiley & Sons, Ltd.